A case study of active learning implementation to develop college students’ problem-solving ability in physical education - Chen, Feifei; Li, Jianpeng; Yu, Hsin-Chang; Xia, Yingying (Edelweiss Applied Science and Technology, 2025)
Active learning has gained recognition as an effective pedagogical approach in higher education, yet its application in physical education remains underexplored. This study addresses the gap by examining how active learning influences physical education undergraduates' skill development, particularly in problem-solving, communication, and critical thinking. The study aimed to investigate physical education students' perspectives on active learning integration in a specific course and assess its impact on their problem-solving abilities. From April to June 2025, semi-structured interviews were conducted with 10 physical education undergraduates (6 males, 4 females). Thematic analysis was applied to the interview transcripts to identify key patterns. Findings confirmed the effectiveness of active learning in physical education courses. Participants reported improvements in communication, critical thinking, and problem-solving skills, attributing these gains to interactive and student-centered teaching methods. The study concludes that active learning is a practical strategy for enhancing physical education undergraduates' problem-solving skills and overall academic performance, advocating for its broader adoption in physical education curricula.